Multifunctional composite phase change material as well as preparation method and application thereof

By combining myristic acid, palmitic acid and paraffin with porous foam materials, a multifunctional composite phase change material is prepared, which solves the problems of low energy conversion efficiency and mismatch of thermal conductivity of traditional phase change materials, and achieves efficient photothermal conversion and solar thermal utilization.

CN119592307AActive Publication Date: 2025-03-11HUNAN INSTITUTE OF ENGINEERING
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411728130.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Traditional phase change materials face problems such as low energy conversion efficiency, mismatch in thermal conductivity, single energy form and high production cost during the energy conversion process, which limits their application potential in multiple energy systems.

Method used

By mixing myristic acid, palmitic acid and paraffin, the disadvantages of high phase change temperature are improved, and combined with porous foam materials to enhance thermal conductivity and light wave absorption capacity, a multifunctional composite phase change material is prepared.

Benefits of technology

It significantly improves the photothermal conversion capacity and solar thermal utilization efficiency, improves the overall thermal effect, and reduces production costs, and has huge application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159676980000121
    Figure BDA0005159676980000121
  • Figure BDA0005159676980000122
    Figure BDA0005159676980000122
  • Figure HDA0005159676990000011
    Figure HDA0005159676990000011
Patent Text Reader

Abstract

The invention discloses a multifunctional composite phase change material as well as a preparation method and application thereof. The multifunctional composite phase change material is prepared from myristic acid, palmitic acid, paraffin and a porous foam material. According to the multifunctional composite phase-change material provided by the invention, the defect of high phase-change temperature of myristic acid and palmitic acid is improved by mixing myristic acid, palmitic acid and paraffin, the multifunctional composite phase-change material has better adaptability in actual photo-thermal conversion application, the photo-thermal conversion capability can be effectively improved, the solar heat utilization efficiency of the multifunctional composite phase-change material can be improved, and the overall heat effect of the multifunctional composite phase-change material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of phase change materials, and in particular to a multifunctional composite phase change material and a preparation method and application thereof. Background Art

[0002] With the continuous growth of energy demand and the diversification of energy structure, the research and application of high-efficiency energy conversion and storage materials have become the key to solving the energy crisis and improving energy efficiency. Phase change materials (PCMs), as a material that can absorb or release a large amount of latent heat through phase changes, have shown great application potential in the fields of thermal energy storage, solar energy utilization, waste heat recovery, power peak regulation, and thermal management of electronic devices. However, traditional phase change materials face a series of challenges in the energy conversion process, which limits their application potential in various energy systems.

[0003] At present, many phase change materials have low phase change enthalpy values, and the energy they can convert during energy absorption and release is limited, which reduces the overall efficiency of energy conversion. At the same time, there is a mismatch between thermal conductivity and energy transfer, especially organic phase change materials often have poor thermal conductivity, which leads to low heat transfer efficiency during energy conversion and prolongs the energy conversion cycle. In addition, some phase change materials have a single energy conversion form and are only suitable for specific scenarios. They cannot achieve effective conversion of multiple energy forms, which limits the breadth of application. Finally, the research and development and production costs of high-performance phase change materials are high, which increases the application cost of the energy conversion system and reduces the economy of the entire system.

[0004] Therefore, how to develop a high enthalpy, high load rate, high thermal conductivity, low-cost composite phase change material that can efficiently realize the conversion between multiple energy forms is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a multifunctional composite phase change material, which improves the disadvantage of high phase change temperature of myristic acid and palmitic acid by mixing myristic acid, palmitic acid and paraffin, and is more adaptable in the application of actual photothermal conversion, can effectively improve the photothermal conversion capacity, improve its solar thermal utilization efficiency, and significantly improve its overall thermal effect.

[0006] According to a first aspect of the present invention, a multifunctional composite phase change material is provided, and the raw materials for preparing the material include: myristic acid, palmitic acid, paraffin and porous foam material.

[0007] The present invention improves the disadvantage of high phase transition temperature of myristic acid and palmitic acid by mixing myristic acid, palmitic acid and paraffin, and cooperates with porous foam material to further enhance thermal conductivity. On the one hand, the prepared multifunctional composite phase change material has shape stability. On the other hand, the porous foam material enhances the light wave absorption capacity of the multifunctional composite phase change material, which is more adaptable to actual photothermal conversion applications, can effectively improve the photothermal conversion capacity, improve its solar thermal utilization efficiency, and can significantly improve its overall thermal effect, and has great application prospects.

[0008] In some embodiments of the present invention, the porous foam material includes at least one of graphite felt, polyurethane foam and carbon nanotube foam.

[0009] According to a second aspect of the present invention, a method for preparing a composite phase change material is provided, comprising the following steps:

[0010] S1. mixing the myristic acid and the palmitic acid and heating and melting them to obtain a myristic acid / palmitic acid binary eutectic mixture;

[0011] S2. mixing the myristic acid / palmitic acid binary eutectic mixture and paraffin and heating and melting them to obtain a myristic acid / palmitic acid / paraffin ternary eutectic mixture;

[0012] S3. The myristic acid / palmitic acid / paraffin ternary eutectic mixture is heated and melted, and then impregnated into a porous foam material to remove impurities to obtain the multifunctional composite phase change material.

[0013] In some embodiments of the present invention, the following steps are included:

[0014] S1. heating and melting myristic acid and palmitic acid, stirring, ultrasonically oscillating, and cooling to obtain a myristic acid / palmitic acid binary eutectic mixture;

[0015] S2. heating and melting the myristic acid / palmitic acid binary eutectic mixture and paraffin, stirring, ultrasonically oscillating, and cooling to obtain a myristic acid / palmitic acid / paraffin ternary eutectic mixture;

[0016] S3.1. The myristic acid / palmitic acid / paraffin ternary eutectic mixture is heated to melt and then an additive is added, and after stirring and ultrasonic oscillation, the mixture is cooled to obtain a composite phase change material;

[0017] S3.2. Heat and melt the optimized composite phase change material, impregnate it into the porous foam material, cool and dry it, remove the excess phase change material, and obtain the multifunctional composite phase change material.

[0018] In some embodiments of the present invention, the porous foam material is further modified.

[0019] In some embodiments of the present invention, the porous foam material modification step comprises:

[0020] The graphite felt is soaked in a mixed solution of sodium citrate and urea for 30 to 60 minutes, taken out after immersion, placed in an oven, the temperature is set at 50°C to 60°C, dried for 2-4 hours, heat cured, and cooled after heat treatment.

[0021] In some embodiments of the present invention, the thermal curing temperature is 100°C to 120°C.

[0022] In some embodiments of the present invention, the heat treatment temperature is 200°C to 250°C.

[0023] In some embodiments of the present invention, the mass ratio of the sodium citrate, the urea and the graphite felt is 2-5:5-10:100.

[0024] Through the modification of sodium citrate and urea, sodium citrate provides a hydration environment to enhance the effect of gas release during the decomposition of urea, thereby forming a more uniform and stable pore structure. The pore structure of the graphite felt is more suitable for the penetration and distribution of phase change materials, which will help to increase the interface contact area between the two and improve the heat transfer efficiency. In particular, phase change materials are usually liquid-solid phase changes, so the phase change material may need to be evenly distributed in the pores of the graphite felt to effectively transfer heat. The modified graphite felt has a higher thermal conductivity and can more efficiently transfer the Joule heat generated by the current passing through the material to the phase change material, thereby improving the electrothermal conversion efficiency. For composite phase change materials, good thermal conductivity ensures that heat can be distributed quickly and evenly, avoiding heat accumulation and uneven temperature.

[0025] The melting point of myristic acid / palmitic acid eutectic mixture is still high, and paraffin with high enthalpy value is expensive. The mixture of the two can not only reduce the phase change temperature, but also effectively reduce the cost. At the same time, the crystallization performance of the eutectic mixture myristic acid / palmitic acid / paraffin eutectic mixture is better than any single phase change material.

[0026] In some embodiments of the present invention, the heating and melting temperature is 75 to 85° C. and the time is 20 to 40 minutes.

[0027] In some embodiments of the present invention, the stirring rate is 150-200 r / min, the temperature is 75-85° C., and the time is 55-65 min.

[0028] In some embodiments of the present invention, the ultrasonic oscillation power is 120-180 W, the oscillation frequency is 70-90 kHz, the temperature is 65-75° C., and the time is 55-65 min.

[0029] In some embodiments of the present invention, the cooling is cooling to room temperature.

[0030] In some embodiments of the present invention, in step S1, the mass ratio of myristic acid to palmitic acid is (50-75):(50-25).

[0031] Although myristic acid and palmitic acid have many advantages, their phase transition temperature is high when they exist alone, which is not suitable for energy storage under some natural conditions, limiting their wide application in thermal storage systems. However, when myristic acid and palmitic acid are mixed, the phase transition temperature can be effectively reduced, and experiments have shown that the effect is most significant when the ratio of myristic acid to palmitic acid is 65:35.

[0032] In some embodiments of the present invention, the mass ratio of the myristic acid / palmitic acid eutectic mixture to the paraffin in step S2 is (20-70): (80-30).

[0033] In some embodiments of the present invention, step S3 further includes modifying the ternary eutectic mixture; and / or; the modification step includes adding a modifier to the ternary eutectic mixture; and / or, the modifier includes carbon nanotubes and a dispersant.

[0034] In some embodiments of the present invention, the mass ratio of the carbon nanotubes to the dispersant is 2 to 5:1.

[0035] In some embodiments of the present invention, the carbon nanotubes include multi-walled carbon nanotubes.

[0036] In some embodiments of the present invention, the carbon nanotubes are multi-walled carbon nanotubes.

[0037] In some embodiments of the present invention, the multi-walled carbon nanotubes have a diameter of 8 to 15 nm and a length of 8 to 14 μm.

[0038] In some embodiments of the present invention, the dispersant comprises polyvinyl pyrrolidone.

[0039] The multi-walled carbon nanotubes in the present invention have ultra-high thermal conductivity and are widely used to improve the thermal conductivity of organic phase change materials, and the improvement effect is obvious. The present invention first mixes the carbon nanotubes and the carbon nanotube dispersant in a mass ratio of 5:1, thereby enabling the carbon nanotubes to be evenly mixed in the organic solution.

[0040] In some embodiments of the present invention, in step S3.1, the mass ratio of the ternary eutectic mixture to the additive is 100:(0-0.4).

[0041] In some embodiments of the present invention, in step S3.1, the heating and melting temperature is 75 to 85° C. and the time is 20 to 40 minutes.

[0042] In some embodiments of the present invention, in step S3.1, the stirring rate is 150-170 r / min, the temperature is 65-75° C., and the time is 55-65 min.

[0043] In some embodiments of the present invention, in step S3.1, the ultrasonic oscillation power is 120-180 W, the oscillation frequency is 70-90 kHz, the temperature is 65-75° C., and the time is 55-65 min.

[0044] In some embodiments of the present invention, in step S3.2, the heating and melting temperature is 75 to 85° C. and the time is 20 to 40 minutes.

[0045] In some embodiments of the present invention, in step S3.2, the impregnation is vacuum impregnation with a vacuum degree of -0.1 MPa and a time of 4 to 6 hours.

[0046] In some embodiments of the present invention, in step S3.2, the cooling is cooling the freezer chamber to 10-15°C.

[0047] According to a third aspect of the present invention, an application of a composite phase change material in the field of thermal management or temperature control is proposed.

[0048] In some embodiments of the present invention, the thermal management field includes the photothermal conversion field or the electrothermal conversion field.

[0049] The present invention improves the disadvantage of high phase transition temperature of myristic acid and palmitic acid by mixing myristic acid, palmitic acid and paraffin, then adds carbon nanotubes and strengthens the thermal conductivity of the myristic acid / palmitic acid / paraffin eutectic mixture, and finally impregnates the optimized myristic acid / palmitic acid / paraffin eutectic mixture into graphite felt, further strengthening the thermal conductivity. On the one hand, the prepared multifunctional composite phase change material has shape stability, and on the other hand, the graphite felt and carbon nanotubes enhance the light wave absorption capacity of the multifunctional composite phase change material, making it more adaptable in actual photothermal conversion applications, effectively improving the photothermal conversion capacity, improving its solar thermal utilization efficiency, and significantly improving its overall thermal effect, thus having great application prospects.

[0050] The electrical conductivity of the myristic acid / palmitic acid / paraffin eutectic mixture is about 10 to 14 S / m, and it cannot convert electrical energy into thermal energy. The electrical conductivity of the multifunctional composite phase change material is 12 orders of magnitude higher than the former, so the contact resistance between the graphite felt, carbon nanotubes and the myristic acid / palmitic acid / paraffin eutectic mixture can generate Joule heat. Therefore, the addition of carbon nanotubes and graphite felt effectively improves the thermal conductivity of the multifunctional composite phase change material while improving the electrothermal response speed, so that the composite material can quickly convert electrical energy into thermal energy during the electrothermal conversion process, and evenly distribute it inside the material, achieving a significant improvement in the electrothermal conversion efficiency.

[0051] In some embodiments of the present invention, the thermal temperature control field includes CPU temperature control or human body temperature regulation.

[0052] The addition of carbon nanotubes and graphite felt enhances the thermal conductivity of the phase change material. The thermal response speed of the composite material is significantly improved, which can quickly adapt to changes in CPU temperature, ensure stable heat dissipation performance even under high load and effectively reduce the CPU operating temperature, thereby extending the service life of the CPU and improving system stability.

[0053] The addition of carbon nanotubes and graphite felt greatly improves the thermal conductivity and thermal response speed of the phase change material, allowing the headband to respond to changes in head temperature more quickly and accurately, reducing the discomfort caused by overheating or overcooling of the head, improving the wearing comfort of the sports headband, and helping athletes stay focused and in the best condition. The addition of graphite felt enhances the mechanical strength and stability of the composite material, allowing the headband to maintain good temperature control performance after frequent use and washing, extending the product life.

[0054] The multifunctional composite phase change material provided by the present invention can improve the utilization efficiency of solar energy by solar water heaters, maximize the heat absorption and heat release heat energy conversion at a suitable phase change temperature, optimize its performance by adding a dispersant, and is less likely to leak than other materials, and has a higher heat exchange efficiency and is more stable. In addition, the preparation method provided by the present invention is simple and easy to promote and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0056] Figure 1 The sample pictures of the multifunctional composite phase change material obtained in Examples 1-2 and Comparative Example 1;

[0057] Figure 2 The SEM images of the graphite felt, the multifunctional composite phase change material obtained in Example 1 and Comparative Example 1;

[0058] Figure 3 The electrothermal conversion device and temperature change diagram of the multifunctional composite phase change material;

[0059] Figure 4 The photothermal device and temperature change diagram of the multifunctional composite phase change material;

[0060] Figure 5 This is a diagram of the temperature control of the human body by using multifunctional composite phase change materials in a sports headband. DETAILED DESCRIPTION

[0061] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0062] The raw materials and sources in the present invention are shown in Table 1 below:

[0063] Table 1. Sources of raw materials

[0064] Material Name purity / % Manufacturer Myristic acid ≥99 Sinopharm Chemical Reagent Co., Ltd. Palmitic acid ≥99 Sinopharm Chemical Reagent Co., Ltd. paraffin ≥99 Dongguan Zhangmutou Donglin Plastic Co., Ltd. Graphite Felt ≥99 Tianjin Carbon Factory Co., Ltd. Multi-walled carbon nanotubes (8-14 μm) ≥99 Shenzhen Suiheng Graphene Technology Co., Ltd. Carbon Nanotube Dispersants - Shenzhen Suiheng Graphene Technology Co., Ltd.

[0065] Note: The raw material purity in the present invention refers to the mass fraction.

[0066] Example 1

[0067] This embodiment prepares a multifunctional composite phase change material, which is the following raw materials by mass fraction:

[0068] Myristic acid 19.5%, palmitic acid 10.5%, paraffin 70%; carbon nanotubes are 0.05% of the total of the first three, and carbon nanotube dispersant is 0.01%.

[0069] A method for preparing a multifunctional composite phase change material comprises the following steps:

[0070] Analytically pure myristic acid, palmitic acid and paraffin were selected as the main phase change materials, multi-walled carbon nanotubes (diameter 8-14 μm), carbon nanotube dispersants were selected as additives, and graphite felt was selected as the porous skeleton;

[0071] S1. Weigh myristic acid and palmitic acid, and then heat them in a water bath at 80°C for 0.5h to completely melt them, stir the melted myristic acid and palmitic acid with a constant temperature magnetic stirrer at 80°C at a speed of 170-200r / min for 1h, then place them in an ultrasonic cleaner and perform ultrasonic oscillation at a power of 120W and an oscillation frequency of 80kHz in a water bath at 80°C for 1h, and cool them at room temperature to obtain a myristic acid / palmitic acid eutectic mixture;

[0072] S2. The obtained myristic acid / palmitic acid eutectic mixture is heated in a water bath at 80°C until completely melted, and then magnetically stirred with paraffin at 80°C at a speed of 170-200 r / min for 1 hour using a constant temperature magnetic stirrer, and then placed in an ultrasonic cleaner for 1 hour at a power of 120 W and an oscillation frequency of 80 kHz in a water bath at 80°C, and then cooled to 15°C in a constant temperature box to obtain a myristic acid / palmitic acid / paraffin eutectic mixture;

[0073] S3.1. The obtained myristic acid / palmitic acid / paraffin eutectic mixture was heated in a water bath at 80°C until it was melted, and multi-walled carbon nanotubes and carbon nanotube aqueous dispersant were added thereto at a mass fraction of 5:1 to obtain a mixture, which was magnetically stirred at a speed of 130-150 r / min at 70°C for 1 h using a constant temperature magnetic stirrer, and then placed in an ultrasonic cleaner with a power of 120 W and an oscillation frequency of 80 kHz, and ultrasonically vibrated for 1 h in a water bath environment at 70°C to obtain a composite phase change material;

[0074] S3.2. Place the composite phase change material in a 70°C drying oven, add graphite felt, vacuum impregnate for 5 hours at a vacuum degree of -0.1Mpa, cool to 15°C in a constant temperature oven, erase excess phase change material, and obtain a multifunctional composite phase change material, as shown in its SEM image. Figure 3 As shown, it can be seen that the phase change material is well adsorbed in the pores and the porous skeleton forms a uniform thermal conductive network.

[0075] The phase change temperature of the multifunctional composite phase change material is 20.1℃ and the phase change latent heat is 178.1J·g -1 , thermal conductivity is 0.91Wm -1 ·K -1 .

[0076] The sample of the multifunctional composite phase change material obtained in the embodiment is shown in FIG. Figure 1 shown.

[0077] The SEM image of the multifunctional composite phase change material obtained in Example 1 is as follows: Figure 2 As shown in (a) in .

[0078] Example 2

[0079] A multifunctional composite phase change material, which differs from Example 1 only in that it includes the following raw materials in mass fractions:

[0080] The amount of multi-walled carbon nanotubes added was changed to 0.1% of the mass of the myristic acid / palmitic acid / paraffin eutectic mixture, and the carbon nanotube dispersant was 0.05%;

[0081] The phase change temperature of the multifunctional composite phase change material is 20°C and the latent heat of phase change is 182.3 J·g -1 , thermal conductivity is 0.98Wm -1 ·K -1 .

[0082] The sample of the multifunctional composite phase change material obtained in Example 2 is shown in FIG. Figure 1 shown.

[0083] The SEM image of the multifunctional composite phase change material obtained in Example 2 is as follows: Figure 2 As shown in (b) in .

[0084] Embodiments 3 to 8

[0085] Embodiments 3 to 8 are methods for preparing a multifunctional composite phase change material, which differ from Embodiment 1 only in that:

[0086] The mass ratios of the myristic acid / palmitic acid / paraffin eutectic mixture and the multi-walled carbon nanotubes are different, and the mass ratios of the myristic acid / palmitic acid / paraffin eutectic mixture and the multi-walled carbon nanotubes are shown in Table 2 below:

[0087] Table 2. Component mass ratio

[0088] Example Quality Ratio <![CDATA[Latent heat of phase change (J·g -1 )]]> <![CDATA[Thermal conductivity (Wm -1 ·K -1 )]]> Example 3 100 / 0.15 175.0 1.05 Example 4 100 / 0.20 169.3 1.1 Example 5 100 / 0.25 168.8 1.12 Example 6 100 / 0.30 167.9 1.15 Example 7 100 / 0.35 167.7 1.14 Example 8 100 / 0.40 167.5 1.15

[0089] Example 9

[0090] The difference between this embodiment and embodiment 1 is that the ratio of the added amount of myristic acid to palmitic acid is 1:1, and the other conditions are the same.

[0091] The phase change temperature of the multifunctional composite phase change material is 20°C and the latent heat of phase change is 166.3 J·g -1 , thermal conductivity is 0.88Wm -1 ·K -1 .

[0092] Example 10

[0093] The difference between this embodiment and embodiment 1 is that the graphite felt is modified graphite felt, and the other conditions are the same, wherein the modification step is:

[0094] A1. Dissolve sodium citrate in deionized water to prepare a 2wt% sodium citrate solution;

[0095] Dissolving urea in sodium citrate solution to obtain a final urea concentration of 5 wt %;

[0096] A2. Soak the graphite felt in a mixed solution of sodium citrate and urea for 60 minutes to ensure that the surface of each layer of graphite felt is evenly coated with the solution;

[0097] A3. Take out the impregnated graphite felt, place it in an oven, set the temperature to 50°C, and dry it for 2 hours;

[0098] A4. Place the dried graphite felt in a furnace for heat curing at 100°C for 1 hour;

[0099] A5. The cured graphite felt is further heated at 200°C for 30 min and then cooled to obtain modified graphite felt.

[0100] Comparative Example 1

[0101] A phase change material, which is different from Example 1 in that the raw materials are only myristic acid, palmitic acid, paraffin and graphite felt.

[0102] A method for preparing a phase change material comprises the following steps:

[0103] S1. Weigh myristic acid and palmitic acid, and heat them in a water bath at 80°C for 0.5 h to completely melt them;

[0104] S2. The melted myristic acid and palmitic acid were magnetically stirred at 80° C. at a speed of 170-200 r / min for 1 h using a constant temperature magnetic stirrer, and then placed in an ultrasonic cleaner for 1 h at a power of 120 W and an oscillation frequency of 80 kHz in an 80° C. water bath environment, and cooled at room temperature to obtain a myristic acid / palmitic acid eutectic mixture;

[0105] S3. The myristic acid / palmitic acid eutectic mixture obtained in step S2 is heated in a water bath at 80° C. until completely melted;

[0106] S4. The melted myristic acid / palmitic acid eutectic mixture and paraffin were magnetically stirred at 80° C. at a speed of 170-200 r / min for 1 h using a constant temperature magnetic stirrer, and then placed in an ultrasonic cleaner for 1 h at a power of 120 W and an oscillation frequency of 80 kHz in an 80° C. water bath environment, and cooled to 15° C. in a constant temperature box to obtain a myristic acid / palmitic acid / paraffin eutectic mixture;

[0107] S5. Place the myristic acid / palmitic acid / paraffin eutectic mixture obtained in step S4 in a 70°C drying oven, add graphite felt, vacuum impregnate for 5 hours at a vacuum degree of -0.1Mpa, cool to 15°C in a constant temperature oven, erase excess phase change material, and obtain multifunctional composite phase change material comparative example 1.

[0108] The phase change temperature of the multifunctional composite phase change material is 22.3℃ and the phase change latent heat is 217.8J·g -1 Thermal conductivity: 0.83Wm -1 ·K -1 .

[0109] The sample of the multifunctional composite phase change material obtained in Comparative Example 1 is shown in FIG. Figure 1 shown.

[0110] The SEM image of the multifunctional composite phase change material obtained in Comparative Example 1 is as follows: Figure 2 As shown in (c) in .

[0111] Comparative Example 2

[0112] The difference between this comparative example and the embodiment is that the carbon nanotubes are replaced by graphene, and the other conditions are the same.

[0113] Test Example 1

[0114] The products obtained in the examples and comparative examples were subjected to electrothermal conversion and photothermal conversion tests and the temperature control test in the sports headband of Example 2. The specific test methods are as follows:

[0115] Electrothermal conversion test:

[0116] DC power supplies with different voltages were used to evaluate Comparative Example 1, Comparative Example 2, Example 2, and Example 4 (25×25×10 mm 3 ) of the electrothermal conversion performance. A multi-channel temperature recorder was used to record the temperature change over time. The electrothermal conversion rate was calculated using formula (1):

[0117]

[0118] Where I, U, and t are the current, voltage, and time during the phase change process, respectively. m and ΔH are the mass and melting enthalpy of the sample, respectively.

[0119] The results are as follows Figure 3As shown, the electrothermal conversion rate of the composite phase change material after adding the additive is improved. Example 10 is as high as 76%. In Example 10, the graphite felt is modified by sodium citrate and urea. Sodium citrate provides a hydration environment to enhance the effect of gas release during the decomposition of urea, thereby forming a more uniform and stable pore structure. The pore structure of the graphite felt is more suitable for the penetration and distribution of the phase change material. The modified graphite felt has a higher thermal conductivity and can more efficiently transfer the Joule heat generated by the current passing through the material to the phase change material, thereby improving the electrothermal conversion efficiency.

[0120] Photothermal conversion test:

[0121] A xenon lamp was used as the light source to study the photothermal conversion performance. The light intensity was maintained at 1.0 sun (100 mW cm -2 ), turn off the light source after 28 minutes of illumination, and let the sample cool naturally at room temperature for 30 minutes. The temperature of graphite felt, comparative example 1, example 2 and example 4 (25×25×10mm 3 ) changes with time. The light-to-heat conversion rate (ω) is calculated by the following formula (2):

[0122]

[0123] Where S, P, and t are the illuminated surface area, the irradiation power of the xenon lamp, and the phase transition time, respectively. m and ΔH represent the mass and melting enthalpy of the sample, respectively.

[0124] The results are as follows Figure 4 As shown, it can be seen that the light-to-heat conversion efficiency of the composite material is greatly improved after adding the additive. It is also found that with the increase in the mass fraction of the additive, the light-to-heat conversion rate of the composite material shows a linear upward trend, reaching a maximum of 90%, which is 20% higher than when no additive is added.

[0125] Sports headband temperature control test:

[0126] The composite phase change material obtained in Example 2 was coated with high molecular weight polyethylene and assembled on the forehead and behind the ears of the headband. Two testers ran at a speed of 8 km / h for 30 minutes in an environment of 37°C, and an infrared thermal imager was used to record the temperature changes before and after exercise.

[0127] The results are as follows Figure 5As shown, compared with conventional headbands, when the two testers wore the headband equipped with composite phase change materials and exercised for 30 minutes, the temperature of the headband part was effectively controlled. Among them, the forehead temperature of tester 1 dropped from 27.3°C to 26.7°C, and the ear base temperature dropped from 27°C to 26.4°C; the forehead temperature of tester 2 dropped from 27.9°C to 26.8°C, and the ear base temperature dropped from 27.3°C to 26.5°C. In Comparative Example 2, compared with the fibrous structure of carbon nanotubes, the stacked structure of graphene is prone to thermal resistance, especially at the contact interface with other components (such as the phase change material matrix). The stacked graphene layers may cause the heat to propagate inside the material to be blocked, and it is impossible to form a continuous and efficient heat conduction channel, thereby affecting the thermal response speed of the phase change material, and it is impossible to achieve effective control of the temperature of the headband part.

[0128] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A multifunctional composite phase change material, characterized in that: The preparation raw materials include: myristic acid, palmitic acid, paraffin and porous foam material.

2. The composite phase change material according to claim 1, characterized in that: The porous foam material includes at least one of graphite felt, polyurethane foam and carbon nanotube foam.

3. A method for preparing a composite phase change material as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1. mixing the myristic acid and the palmitic acid and heating and melting them to obtain a myristic acid / palmitic acid binary eutectic mixture; S2. mixing the myristic acid / palmitic acid binary eutectic mixture and paraffin and heating and melting them to obtain a myristic acid / palmitic acid / paraffin ternary eutectic mixture; S3. The myristic acid / palmitic acid / paraffin ternary eutectic mixture is heated and melted, and then impregnated into a porous foam material to remove impurities to obtain the multifunctional composite phase change material.

4. The method for preparing a composite phase change material according to claim 3, characterized in that: The mass ratio of myristic acid to palmitic acid in step S1 is (50-75):(50-25).

5. The method for preparing the composite phase change material according to claim 3, characterized in that: The mass ratio of the binary eutectic mixture to the paraffin in step S2 is (20-70):(80-30).

6. The method for preparing a composite phase change material according to claim 3, characterized in that: Step S3 further includes modifying the ternary eutectic mixture; and / or; the modification step includes adding a modifier to the ternary eutectic mixture; and / or, the modifier includes carbon nanotubes and a dispersant.

7. The method for preparing a composite phase change material according to claim 6, characterized in that: The dispersant includes polyvinyl pyrrolidone.

8. The method for preparing a composite phase change material according to claim 6, characterized in that: In step S3, the mass ratio of the ternary eutectic mixture to the modifier is 100:(0-0.4).

9. Application of the composite phase change material according to claim 1 or 2 in the field of thermal management or temperature control.

10. The use according to claim 9, characterized in that: The thermal management field includes the field of photothermal conversion or the field of electrothermal conversion.

Citation Information

Patent Citations

  • Solar phase change energy storage composite material for floor radiant heating and preparation method of composite material

    CN102676125A

  • Highly-heat-conductive shaped phase-change heat-storage material and preparation method thereof

    CN105154017A

  • Novel metal base material shaping heat accumulating material and preparation method thereof

    CN105295847A

  • Eutectic phase-change material for energy conservation of building exterior walls and preparation method of eutectic phase-change material

    CN105950117A

  • Graphite felt phase change composite for phase change energy storage device and manufacturing method of graphite felt phase change composite

    CN106440905A